АКЦІОНЕРНІ УГОДИ ЯК СПОСІБ ВРЕГУЛЮВАННЯ КОРПОРАТИВНИХ ВІДНОСИН - Zhabskyi, V.I. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2010)
The author analyzes a legal nature of stock holders’ agreements. A special attention is given to a judiciary law on acknowledgement of stock holder’s agreements to be invalid by the courts. Based on the analysis, changes into the legislation are offered.